2022
DOI: 10.3390/antibiotics12010010
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of KPC-31 and OXA-181 Klebsiella pneumoniae Resistant to New Generation of β-Lactam/β-Lactamase Inhibitor Combinations

Abstract: Background: Carbapenem resistant Klebsiella pneumoniae (cr-Kp) causes serious infections associated with a high mortality rate. The clinical efficacy of ceftazidime/avibactam (CZA), meropenem/vaborbactam (M/V), and imipenem/relebactam (I/R) against cr-Kp is challenged by the emergence of resistant strains, making the investigation and monitoring of the main resistance mechanisms crucial. In this study, we reported the genome characterization of a Klebsiella pneumoniae strain isolated from a critically ill pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…According to international guidelines, a protocol for monitoring antibiotic resistance has been active in our hospital since 2015. As already described in previous reports [ 13 , 41 ], the local epidemiological scenario has shown an increased variability in terms of circulating variants, particularly among carbapenemase-producing Gram-negative bacteria, such as Escherichia coli bla VIM and Enterobacter spp. class A carbapenemase producers.…”
Section: Discussionmentioning
confidence: 69%
“…According to international guidelines, a protocol for monitoring antibiotic resistance has been active in our hospital since 2015. As already described in previous reports [ 13 , 41 ], the local epidemiological scenario has shown an increased variability in terms of circulating variants, particularly among carbapenemase-producing Gram-negative bacteria, such as Escherichia coli bla VIM and Enterobacter spp. class A carbapenemase producers.…”
Section: Discussionmentioning
confidence: 69%
“…However, with its widespread use in clinical practice, we were alarmed by the explosion in the detection of bla KPC-2 or bla KPC-3 mutants after ceftazidime-avibactam treatment. Most of these mutants showed high-level resistance to ceftazidime-avibactam, such as bla KPC-31 [ 27 ], bla KPC-33 [ 20 ], etc. Moreover, the increased bla KPC expression, membrane porin deficiency and the co-production of KPC variants and other carbapenemases could mediate both carbapenem and ceftazidime-avibactam resistance [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bla KPC variants tend to have a distinctive antimicrobial susceptibility phenotype. The majority of KPC mutants exhibit the ability to confer resistance to ceftazidime-avibactam (MIC range 16 - > 128 mg/L), mainly through the enhanced hydrolytic activity towards ceftazidime such as bla KPC-31 [ 27 ], bla KPC-41 [ 29 ] and reduced inhibition ability of avibactam such as bla KPC-109 [ 28 ], bla KPC-53 [ 19 ]. To note, most KPC variants could mediate susceptibility to carbapenems (especially imipenem) other than bla KPC-87 [ 30 ], bla KPC-109 [ 28 ] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous resistance to CZA and MEM is rare. Muresu et al reported [ 39 ] a K. pneumoniae strain harboring bla KPC-31 and bla OXA-181 that was resistant to both CZA and MEM, but the cloning of bla KPC-31 [ 40 ] and bla OXA-181 [ 41 ] did not show MEM resistance. Arcari et al reported [ 42 ] a K. pneumoniae strain carrying bla KPC-154 that showed MEM resistance, but resistance was not observed when the bla KPC-154 gene was cloned.…”
Section: Discussionmentioning
confidence: 99%